Evidence for distinctive changes in the solar wind helium abundance in solar cycle 24. Issue 1 (13th February 2021) - , Yogesh; Chakrabarty, D; Srivastava, N
ABSTRACT: The relative abundance of alpha particles with respect to protons, usually expressed as A He = ( n α / n p )*100, is known to respond to solar activity, although changes in its behaviour in the last four solar cycles are not known. In this letter, by systematically analysing inter-calibrated A He data obtained from the first Lagrangian point of the Sun–Earth system, we show that A He variations are distinctively different in solar cycle 24 as compared to the last three cycles. The frequency of A He = 2–3 per cent events is significantly higher in slow/intermediate solar winds in solar cycle 24 as opposed to the dominance of the typical A He = 4–5 per cent events in the previous three cycles. Further, the occurrence of A He > 10 per cent events is significantly reduced in cycle 24. Not only that the changes in delay of A He with respect to peak sunspot numbers are less sensitive to changes in solar wind velocity in cycle 24. The investigation suggests that the coronal magnetic field configuration started undergoing systematic changes starting from cycle 23 and this altered magnetic field configuration affected the way helium got processed and depleted in the solar atmosphere.